COMBINED PIPRECIA METHOD AND MODIFIED FUCA METHOD FOR SELECTION OF LATHE - Duc Trung, Do; Truong, Nguyen Xuan; Thinh, Hoang Xuan (Journal of Applied Engineering Science, 2022)
The choice of technological equipment in general or lathe in particular has a great influence on the efficiency of the machining processes. Lathes are often evaluated by many criteria, both quantitative and qualitative. Sometimes the criteria employed by the methods are opposite to each other. Hence the choice of lathe is usually made through the evaluation of multiple criteria, which is known as “Multi-Criteria Decision Making – MCDM”. In the research was used PIPRECIA method to determine the weights of the criteria. Modifications to FUCA method were then implemented. The combination of PIPRECIA method and the modified FUCA method were applied to the lathe selection in two cases. In both cases the best and worst alternatives were determined in the same way as when using the CURLI method. This confirms the correct implementation of the FUCA method modification, and the combination of PIPRECIA and the modified FUCA method turns out to be a right approach in the selection of lathes. Details that need to be considered in future research were also mentioned in this study.
Keywords: MCDM, PIPRECIA, modified FUCA method, CURLI, lathe selection